PENGARUH PENGGUNAAN TEKNOLOGI AUGMENTED REALITY (AR) TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SAINS DI KELAS VI SEKOLAH DASAR - Aditya Yoga Pratama; Eka Sastrawati; Muhammad Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of using Augmented Reality (AR) technology on student learning outcomes in science subjects, specifically on the Solar System material in sixth grade at SD Negeri 216/IV Kota Jambi. This research employed a quasi-experimental design with a Nonequivalent Control Group Design. The research sample consisted of 30 students divided into an experimental group (15 students) who received learning using AR technology and a control group (15 students) who used conventional learning. The research instrument was a multiple-choice test consisting of 20 questions that had been tested for validity and reliability. Data analysis used paired sample t-test and independent sample t-test. The results showed that there was a significant effect of using AR technology on student learning outcomes with a significance value of 0.000 < 0.05. The average post-test score of the experimental group was 76.67, higher than the control group at 37.33, with t count value of 14.473 > t table 2.048. This study proves that AR technology is effective in improving student learning outcomes in understanding abstract concepts such as Solar System material because it presents interactive and contextual three-dimensional visualizations.